2013
DOI: 10.1177/0265407513481445
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits, loneliness, and attitudes toward aloneness in adolescence

Abstract: Within a dual-level model of personality, loneliness, and attitudes toward aloneness can be regarded as phase-specific adaptations that are influenced by personality traits. Therefore, we examined the associations between personality traits (i.e., the Big Five, sociotropy, and autonomy), loneliness, and attitudes toward aloneness in two samples of late adolescents (N = 1388 and N = 419). A specific pattern of associations was found that replicated across samples. Lower scores on agreeableness and stronger conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
82
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 40 publications
13
82
0
4
Order By: Relevance
“…Furthermore, the present study adds to the ambiguous findings on the association between loneliness and both openness and conscientiousness. With regard to openness, the present study suggests that loneliness is unrelated to this trait, thereby supporting previous finding (Teppers et al, 2013;Vanhalst et al, 2013). Similarly, as van der Aa et al (2009) and Mund and Neyer (2016), we found a negative association between loneliness and conscientiousness.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the present study adds to the ambiguous findings on the association between loneliness and both openness and conscientiousness. With regard to openness, the present study suggests that loneliness is unrelated to this trait, thereby supporting previous finding (Teppers et al, 2013;Vanhalst et al, 2013). Similarly, as van der Aa et al (2009) and Mund and Neyer (2016), we found a negative association between loneliness and conscientiousness.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the effects of loneliness appeared to be independent of the age groups assessed. The findings of the present study align well with prior findings from cross-sectional and shorter-term longitudinal studies (Hensley et al, 2012;Saklofske & Yackulic, 1989;Stokes, 1985;Teppers et al, 2013;van der Aa et al, 2009;Vanhalst et al, 2013;Vanhalst et al, 2012) by demonstrating that loneliness is positively associated with neuroticism and negatively with extraversion and agreeableness. Furthermore, the present study adds to the ambiguous findings on the association between loneliness and both openness and conscientiousness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this context, we can list the following factors that are potentially between network position and level of satisfaction with social relationships: the need to belong (Leary, Kelly, Cottrell and Schreindorfer, 2013;Pickett, 2004), preference for loneliness (Burger, 1995), sensitivity to rejection (London, Downey, Bonica and Paltin, 2007), personality features (Teppers et al, 2013), self-esteem (Çivitci and Çivitci, 2009), conviction of one's own effectiveness (Wei, Russell and Zakalik, 2005) or even genetic factors . Any of these could be the reason for a different assessment of analogous peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…r = .07; Teppers et al, 2013) whereas others found negative relations (e.g. Some studies found positive relations (e.g.…”
Section: Conscientiousness and Lonelinessmentioning
confidence: 93%